2017
DOI: 10.1103/physrevx.7.021036
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Contact between a Droplet and an Atomically Smooth Substrate

Abstract: When a droplet gently lands on an atomically smooth substrate, it will most likely contact the underlying surface in about 0.1 s. However, theoretical estimation from fluid mechanics predicts a contact time of 10-100 s. What causes this large discrepancy, and how does nature speed up contact by 2 orders of magnitude? To probe this fundamental question, we prepare atomically smooth substrates by either coating a liquid film on glass or using a freshly cleaved mica surface, and visualize the droplet contact dyna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 50 publications
2
49
0
Order By: Relevance
“…Neglecting intermolecular forces between the droplet and surface, they hypothesized that during spreading the droplet compresses the gas underneath and creates a barrier between the droplet and surface. The presence of the air film has been experimentally demonstrated by several recent studies [40][41][42]56]. For our low-velocity impacts, we observe that the droplet does eventually penetrate the air film during spreading and comes into contact with the surface.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Neglecting intermolecular forces between the droplet and surface, they hypothesized that during spreading the droplet compresses the gas underneath and creates a barrier between the droplet and surface. The presence of the air film has been experimentally demonstrated by several recent studies [40][41][42]56]. For our low-velocity impacts, we observe that the droplet does eventually penetrate the air film during spreading and comes into contact with the surface.…”
Section: Resultssupporting
confidence: 71%
“…This hypothesis is plausible since recent work has shown that the atmospheric conditions have a significant influence on droplet dynamics, as, for example, in droplet splashing [12,[26][27][28][29][30], air entrainment [31][32][33], the coalescence of droplets on liquid surfaces [34], air cushioning of an impacting drop [35,36,38], and bouncing droplets on superhydrophobic and hydrophilic surfaces [37,38]. In many cases, it was shown that an impacting drop does indeed skate over an entrapped air layer before wetting the surface [38][39][40][41][42]. Thus, the open questions are (i) whether the air film has a significant influence on low-velocity droplet impact and (ii) how the extra parameter introduced by Lee et al can be related to the wetting properties of the fluid [43] so that the maximum radius can be predicted from the combined models of Laan et al and Lee et al…”
Section: Introductionmentioning
confidence: 97%
“…1B and Movies S3-S5, the droplets experience three stages after release from a height h = 5 mm: impact, bouncing, and hanging. At the initial impact stage, the droplet thins an air layer between the droplet and surface of the solution, but there is no liquidliquid contact, and the droplet recoils from the surface (25)(26)(27). After bouncing away, the droplet returns to and rests on the surface, and the air layer continually thins until the two aqueous phases establish contact and the droplet begins to spread on the surface (26).…”
Section: Resultsmentioning
confidence: 99%
“…The inertial dynamics are unable to account for the effects of ambient pressure [21,24]. Recent studies [18,[25][26][27][28][29][30][31] do not provide confirmation about the potential formation of an air film underneath the lamella tip before the splash initiation. A model based on the lamella aerodynamics [20] appears to be suitable for applications to a variety of conditions [20][21][22][32][33][34][35] and will be used in the present study.…”
mentioning
confidence: 99%